High-Throughput Fluorescent Tagging of Full-Length Arabidopsis Gene Products in Planta - Tian, Guo-Wei (American Society of Plant Biologists, 2004)
We developed a high-throughput methodology, termed fluorescent tagging of full-length proteins (FTFLP), to analyze expression patterns and subcellular localization of Arabidopsis gene products in planta. Determination of these parameters is a logical first step in functional characterization of the approximately one-third of all known Arabidopsis genes that encode novel proteins of unknown function. Our FTFLP-based approach offers two significant advantages: first, it produces internally-tagged full-length proteins that are likely to exhibit native intracellular localization, and second, it yields information about the tissue specificity of gene expression by the use of native promoters. To demonstrate how FTFLP may be used for characterization of the Arabidopsis proteome, we tagged a series of known proteins with diverse subcellular targeting patterns as well as several proteins with unknown function and unassigned subcellular localization.